PENGARUH PENGGUNAAN METODE BERMAIN PERAN DALAM PEMBELAJARAN TEMATIK PADA MUATAN PEMBELAJARAN IPS UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS V DI SDN GENDINGAN 2 - Elina Rusita Dewi; Djoko Hari Supriyanto; Yes Matheos Lasarus Malaikosa (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The role-playing method is learning through the development of students' imagination and passion by the way students play a character, both life and death figures, this method develops passion, responsibility, and skills in using the material learned. In the application of the role-playing method, students seem more interested in following the learning process because the learning process becomes less boring and students can be more creative according to their wishes. In addition, the application of this method affects student learning outcomes to be further improved because students follow the thematic learning process by using the role-playing method with enthusiasm and really so that students can understand the material provided well.